Case Report: Individualized circulating tumor DNA monitoring guides olaparib adjuvant therapy: an early-stage breast cancer case with somatic BRCA2 mutation - You, Qiuting; Gong, Longlong; Chen, Yi; Dinglin, Xiaoxiao; Cheng, Ziliang; Xia, Qian; Xie, Jinxia; Zhao, Jianli; Su, Fengxi (Frontiers in Oncology, 2026)
BackgroundCirculating tumor DNA (ctDNA) has demonstrated a strong predictive capacity for recurrence in early-stage breast cancer compared with imaging examinations. However, there remains a paucity of robust clinical evidence to guide the adjustment of adjuvant therapy based on minimal residual disease (MRD) status in early-stage breast cancer.Case presentationA 69-year-old female patient with early-stage triple-negative breast cancer (TNBC) with somatic BRCA2 mutations exhibited an exceptional response to adjuvant therapy with olaparib. Personalized ctDNA monitoring, utilizing a tumor-informed approach, was employed alongside imaging examinations and tumor biomarker testing to monitor tumor recurrence. MRD positivity was detected at four months and approximately one-month post-treatment discontinuation. Resumption of olaparib therapy resulted in a negative MRD status, while imaging examinations consistently demonstrated no evidence of recurrence in the patient.ConclusionsThis report underscores the potential benefit of olaparib for early-stage TNBC patients with somatic BRCA2 mutations and the utility of serial ctDNA monitoring for tailoring individualized treatment strategies.